Compression pre-stapler firing and post-ignition wait during sleeve gastrectomy: a prospective randomized trial - Sermet, Medeni (São Paulo Medical Journal, 2025)
BACKGROUND: Insufficient research exists on the stapling technique in and duration of laparoscopic sleeve gastrectomy (LSG). OBJECTIVES: This study aimed to assess the clinical outcomes using a 30-second precompression and post-firing waiting time without extra support for the stapling line. DESIGN AND SETTINGS: Randomized controlled prospective study at a university hospital. METHODS: This study included 120 patients treated between January 2022 and February 2023. The patients were divided into the non-waiting group (T0) and waiting group (T1), each with 60 patients. Perioperative complications were analyzed using statistical tests. RESULTS: The waiting group (T1) showed a significant reduction in the number of intraoperative bleeding points requiring intervention compared with the non-waiting group (T0) (81 versus 134, P < 0.05). In T0, postoperative C-reactive protein (CRP) levels increased (P < 0.05) and hemoglobin levels decreased significantly (P <0.05). The study recorded 22 postoperative complications, accounting for 18.3% of all cases during the 30-day postoperative period. CONCLUSIONS: The study concluded that the 30 sec + 30 sec stapling technique reduces perioperative bleeding, length of stay, and serious complication rates and is practical and effective for LSG. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov with registration code NCT05703035; link: https://clinicaltrials.gov/ct2/show/NCT05703035.